Efecto del riego con aguas ricas en arsénico sobre un cultivo de rúcula (Eruca sativa L.) - Castillo, Nadia Sabiela (2013)
Large areas of Chaco Pampean plain have aquifers containing high arsenic values. The use of these waters to irrigate horticultural species, in particular, those for fresh consumption could have direct effects on human health as well as on agricultural soils. The aim of this work was to evaluate the arsenic content in the species Eruca sativa L (arugula) and also to evaluate the soil when applying irrigation with waters prepared in the laboratory with different arsenic concentration and alkalinity. An assay with DBCA design and factorial arrangement was performed (soil type/alkalinity/As level) employing two types of soils with different textures (sandy loam and silty loam), developing 20 plants per pot. Pots were kept at 90% of field capacity with daily irrigation using water of different alkalinity and arsenic concentration. Three concentrations of arsenic were used (100, 250 and 500 μg.L-1), employing the starting water (not modified by As) as witness. Variables evaluated were vegetal dry matter and arsenic concentration in plant and soil. Irrigation conditions affected the arsenic content in the plant reaching toxicity levels similar to those cited in the literature, particularly in silty loam soil. Although the increase of arsenic concentration is evident in vegetal, it is not possible to establish a reliable relation between the arsenic concentration in the vegetal and the plant yield. Moreover, the arsenic content in the soil also increased with the irrigation showing higher levels in silty loam soil without reaching hazard limits in the first sowing. It is possible to conclude that although the arsenic concentration in fresh vegetal is within limits established by the legislation, its consumption could contribute to the daily intake of arsenic which, in turn, could add to the hazard of drinking water with arsenic.